Voluntary Activation is Reduced in Both the More- and Less-Affected Upper Limbs after Unilateral Stroke - Bowden, Jocelyn L.; Taylor, Janet L.; McNulty, Penelope A. (Frontiers in Neurology, 2014)
Objective: Measurement of voluntary activation gives an indication of neural drive to the muscle. This study aimed to identify the site of impairment in neural drive during voluntary contractions post-stroke. Methods: Elbow-flexor voluntary activation was assessed bilaterally for 10 stroke patients (mean 61.2±12.3 years) and 6 age-matched controls (61.3±14.0 years) by stimulating either the peripheral nerve or the motor cortex during maximal voluntary contractions. Any additional evoked force during maximal contractions implies neural drive is incomplete. Peripheral stimulation can detect deficits at or above the stimulation level, while cortical stimulation can identify suboptimal supraspinal output. Results: Impairments were apparent on the less-affected side in addition to the more-affected side after stroke in voluntary activation, torque and EMG response. Maximal torque was reduced by 44% on the more-affected and 31% on the less-affected side compared to healthy controls (p<0.001). Peripheral voluntary activation was reduced to 81% on the more-affected side and 86% on the less-affected side, with healthy subjects at 96% (p<0.05). Although EMG was bilaterally impaired after stroke, the pattern of response was different between sides. Voluntary activation could not be calculated for cortical stimulation post-stroke due to variability in the evoked force, but EMG results from cortical stimulation showed significant differences in the neural drive to each side. Conclusions: Voluntary activation is impaired bilaterally in the upper-limb after stroke, with reduced cortical connectivity on the more-affected side. Significance: Although the muscle itself did not change post-stroke, altered descending drive and connectivity were the critical factors explaining post-stroke paresis.